Design of liquefaction process of biogas using Aspen HYSYS simulation - Ahmad, Nurjehan Ezzatul; Mel, Maizirwan; Sinaga, Nazaruddin (Penerbit Akademia Baru, 2018)
The liquefaction of biogas appears to be an appropriate solution in cases where logistics constraints arise due to the absence of a transportation network. In liquid form, biomethane is easy to transport to its point of use. Aspen HYSYS, computer-aided process design programs, widely used in chemical and thermodynamic process industries, which has built-in process models that can effectively simulate the liquefaction process. In this study liquefaction process of biogas was simulated in Aspen HYSYS with the aim to at assess the technology using cryogenic process to liquefy the biogas and obtain the liquefied biomethane and CO2 as a by-product through the simulation results. The parameters such as biogas feed, temperature and pressure are obtained from the case study from Havys Biogas Power Plant owned by Cenergi Sdn. Bhd. Hence, with a working principle of cryogenic process, a design of the process of liquefaction of biogas was simulated in Aspen HYSYS simulation environment where it consists of three stages, which are pre-cooling stage, liquefaction stage and sub-cooling stage. As a result, with a biogas feed of 1,500 m3/h consists of 60% CH4 and 40% CO2 at 200 kPa and 35˚C, liquefied biomethane were obtained from the design of the simulation with a purity of 99% and liquid CO2 was also obtained as a by-product of the liquefaction process.